PENGUKURAN BERAT RADIONUKLIDA 137Cs DALAM LARUTAN PELAT ELEMEN BAKAR U3Si2/Al DENSITAS 4,8 gU/cm3 PASCA IRADIASI DENGAN METODE KOLOM KROMATOGRAFI - Boybul; Yanlinastuti; Noerpitasari, Erlina; Carlos Sihotang, Juan; Fauzi Rahmatullah, Helmi; Nugroho, Arif; Sukron Fajrin Husein, Mohammad; Sigit, Rohmad; Br Ginting, Aslina; WIdodo, Susilo (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
The burn up value of the fuel is one of the parameters that must be known in the post-irradiation examination. The determination of burn up aims to determine the performance of U3Si2/Al fuel after being used in the reactor. One of the isotops that can be used as an indicator of burn up is 137Cs because it has a long half-life (T1/2) of 30.17 years with a fission yield of 6.26%. Therefore, in this study, a separation was carried out to determine the amount of 137Cs in the U3Si2/Al fuel solution post irradiation using the cation exchange column method using zeolit from Lampung along with its recovery rate. The solution of irradiated U3Si2/Al fuel from Top (T), Middle (M), and Bottom (B) position, was each pipetted in a duplicate manner (duplo) in an amount of 50 µL and added with 2 mL of 0.1 M HNO3. The solutions were then measured activity using a gamma spectrometer to obtain the initial weight of 137Cs radionuclide. The solution was then inserted into a chromatography column containing 700 mg of zeolit Lampung and allowed to flow under vacuum condition. The separation results showed that 137Cs was bound to the zeolit in the form of 137Cs-zeolit solid phase, while other isotops remained in the liquid phase. The solid 137Cs-zeolit and 137Cs in the supernatant were then measured with a gamma spectrometer to determine the weight of 137Cs bound to the zeolit. The measurement results showed that the average initial weight of 137Cs (before separation) were 7.49 × 10-3 µg/gFEP and dan 6.97 × 10-3 µg/gFEP for T1 and T2 from top section, 10.50 × 10-3 µg/gFEP for M1 from Middle section, and dan 8.43 × 10-3 µg/gFEP and 8.76 × 10-3 µg/gFEP for B1 and B2 from Bottom section, respectively. After separation, the average weight of 137Cs were 7.43 × 10-3 µg/gFEP and 6.82 × 10-3 µg/gFEP for T1 and T2, 10.10 × 10-3 µg/gFEP for M1, and 8.32 × 10-3 µg/gFEP and 8.41 × 10-3 µg/gFEP for B1 and B2, respectively. From the weight of 137Cs before and after separation, the average separation recovery with the cation exchange chromatography column method using zeolit was obtained at 97.748%. This recovery value indicates that zeolit Lampung is highly selective for absorbing 137Cs in the solution of irradiated U3Si2/Al fuel.